DETERMINAÇÃO SIMULTÂNEA DE METAIS E ENXOFRE POR ICP-OES EM RESÍDUOS DE DESTILAÇÃO DE PETRÓLEO - Gabriel T. Druzian; Cristiano K. Giesbrecht; Francisco C. Rosa; Regina C. L. Guimarães; Ricardo A. Guarnieri; Paola A. Mello; Érico M. M. Flores (Química Nova)
A method for digestion of crude oil distillation residues (atmospheric residue, AR and vacuum residue, VR) using microwave-induced combustion (MIC) was developed for simultaneous determination of metals (Ba, Co, Fe, Mg, Mn, Ni and V) and sulfur by inductively coupled plasma optical emission spectrometry (ICP-OES). Samples were wrapped in polyethylene films and combusted using 20 bar of oxygen. Nitric acid solutions were evaluated using 5 min of reflux after combustion. Accuracy was evaluated using certified reference material and comparison with the results obtained by microwave-assisted wet digestion (MAWD). No statistical difference was observed between the certified values and those obtained using MIC as well as between the values obtained using MAWD or MIC. In spite of both methods have been apparently suitable for crude oil digestion, MIC was preferable in view of the possibility of using 3 mol L-1 HNO3 as absorbing solution. Furthermore, it is important to notice that using MIC, C content in digests was lower than 10 mg L-1, preventing interferences in ICP-OES. In addition, the simultaneous digestion of eight samples was possible in less than 30 min and without using concentrated acids and/or longer heating times, making the proposed method well-suited for routine analysis.